Association Between the Fcyriiia-158v-F Polymorphism and Periodontitis - Vidal-Soto, R (UNIV COSTA RICA, FAC ODONTOLOGIA, 2017)
The multifactorial etiology of periodontitis is recognized, where genetic and environmental factors interact to produce the disease and modify its clinical expression The aim of this study is to determine the association between the presence of the polymorphism for IgG subclass III A receptor (FCYRIIIA-158V-F) and severe periodontitis. Materials and Methods: The study sample was composed of 150 patients: 32 patients with aggressive periodontitis, 71 patients with chronic periodontitis, and 47 clinically healthy volunteers without periodontitis. Peripheral blood samples, approximately 20 mu l, were obtained. DNA extraction was carried out from the FTAelute micro-cards. The selected polymorphisms were amplified by PCR. Results: The genotypic frequencies of the three groups evaluated met the Hardy-Weinberg equilibrium (Chi-square test, p-value> 0.05, 95% CI). The difference between the periodontitis (chronic and aggressive peridontitis) group and the group of healthy individuals was statistically significant for the presence of the T allele (p <= 0.004), with an OR of 4.03 (95% CI), the sensitivity to 93% and specificity to 23%, with a positive predictive value of 72% and a negative predictive value of 61%. Conclusions: A statistically significant association was found between the presence of the T allele in the polymorphism of FCYRIIIA-158V-F and the diseased condition (periodontitis group), suggesting that the T allele possesses a higher probability of developing severe periodontitis. Due to the importance of identifying subjects susceptible to periodontitis we recommend further studies.